Development of a self-care guideline to prevent rehospitalization in stroke patients: a modified Delphi study - Putra, Komang Ardidhana Nugraha; Suyasa, I Gede Putu Darma; Kamaryati, Ni Putu; Dharmapatni, Ni Wayan Kesari (Jurnal Ners, 2024)
Introduction: Since 2007, the number of stroke cases in Indonesia has continued to increase. Stroke patients who have passed the acute phase of stroke still have a risk of recurrent stroke and rehospitalization. This study aimed to develop self-care guidelines to prevent the rehospitalization of stroke patients. Methods: A three-round modified Delphi study was applied to a panel of 24 experts with different fields of expertise, consisting of doctors, nurses, families, and patients. In the first round, data were collected through a literature review and semi-structured interviews. In the second and third rounds, data were collected using a survey questionnaire on a 9-point Likert scale. Results: The first round produced seven themes around self-care activities, including drug therapy, physical exercise, diet and nutrition, stress management, self-motivation, functional status screening, and control for risk factors. In the second round, all types of self-care in the first round were agreed upon for content in preparing the guidebook. The third round resulted in agreement on the guidebook that had been designed, with scores of 8 and above by 100% of the expert panel. Conclusions: The development of a self-care guidebook to prevent rehospitalization of stroke patients through a three-round Delphi study has reached a consensus among the entire panel of experts.  Further research by testing guidebooks in the healthcare system is needed to determine their effectiveness in preventing re-hospitalization in stroke patients.